Maternal near miss and predictive ability of potentially life-threatening conditions at selected maternity hospitals in Latin America. Issue 1 (December 2016) - De Mucio, Bremen; Abalos, Edgardo; Cuesta, Cristina; Carroli, Guillermo; Serruya, Suzanne; Giordano, Daniel; Martinez, Gerardo; Sosa, Claudio; Souza, João
Abstract Background Every year millions of women around the world suffer from pregnancy, childbirth and postpartum complications. Women who survive the most serious clinical conditions are regarded as to have experienced a severe acute maternal complication calledmaternal near miss (MNM). Information about MNM cases may complement the data collected through the analysis of maternal death, and was proposed as a helpful tool to identify strengths and weaknesses of health systems in relation to maternal health care. The purpose of this study is to evaluate the performance of a systematized form to detect severe maternal outcomes (SMO) in 20 selected maternity hospitals from Latin America (LAC). Methods Cross-sectional study. Data were obtained from analysis of hospital records for all women giving birth and all women who had a SMO in the selected hospitals. Univariate and multivariate adjusted logistic regression models were used to assess the predictive ability of different conditions to identify SMO cases. In parallel, external auditors were hired for reviewing and reporting the total number of discharges during the study period, in order to verify whether health professionals at health facilities identified all MNM and Potentially life-threatening condition (PLTC) cases. Results Twenty hospitals from twelve LAC were initially included in the study and based on the level of coverage, 11 hospitals with a total of 3, 196records were included for the final analysis. The incidence of SMO and MNM outcomes was 12.9 and 12.3 per 1, 000 live births, respectively. The ratio of MNM to maternal death was 19 to 1, with a mortality index of 5.1 %. Both univariate and multivariate analysis showed a good performance for a number of clinical and laboratory conditions to predict a severe maternal outcome, however, their clinical relevance remains to be confirmed. Coherence between health professionals and external auditors to identify SMO was high (around 100 %). Conclusions The form tested, was well accepted by health professionals and was capable of identifying 100 % of MNM cases and more than 99 % of PLTC variables. Altered state of consciousness, oliguria, placenta accrete, pulmonary edema, and admission to Intensive Care Unit have a high (LR+ ≥80) capacity to anticipate a SMO.